Phenotypic markers of oral keratinocytes seeded on two distinct 3D oral mucosa models - Basso, Fernanda G. [UNESP]; Pansani, Taisa N. [UNESP]; Marcelo, Cyntia L.; de Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP]; Feinberg, Stephen E. (Elsevier, 2018)
This study validates the use of a full-thickness oral mucosa model for in vitro studies with a collagen type I matrix, by comparison of this model with two other 3D oral mucosa models: human-sourced and porcine acellular dermal matrices (AlloDerm®/Strattice®, respectively). For the collagen matrix model, gingival fibroblasts were seeded either onto the dermal side of the AlloDerm® and Strattice® matrices or within the collagen matrices in complete culture medium (DMEM). For all scaffolds, DMEM was replaced every 24 h up to 72 h. For the full-thickness oral mucosa models, 72 h after fibroblast seeding, oral keratinocytes were seeded on the epidermal sides of AlloDerm® and Strattice® matrices or collagen matrices. All matrices and models were subjected to histological analysis, complementing phenotypic characterization by evaluation of glucose consumption, cell proliferation, gene expression and synthesis of growth factors. A higher fibroblast ratio was observed for the collagen matrix, in which the distribution of gingival fibroblasts was also more homogeneous. Metabolism, proliferation, and gene expression and synthesis of VEGF of these cells were also increased for the collagen matrix. All matrices provided a suitable substrate for oral keratinocytes adhesion, proliferation, and phenotypic expression; however, higher proliferation, stratification, and differentiation were noted when oral keratinocytes were seeded on the dermal matrices.
Keywords: Cell culture techniques; Gingival fibroblasts; Organotypic cell culture